p53 gain-of-function mutations promote metastasis via ENTPD5 upregulation and enhanced N-glycoprotein folding - Timofeev, Oleg (Mol Cell Oncol, 2017)
Mutations in cancer abolish normal tumor suppressive functions of tumor protein p53 (TP53, best known as p53) and convert it into an oncogene. We recently reported the identification of ectonucleoside triphosphate diphosphohydrolase 5 (ENTPD5) as a transcriptional target of mutant p53 that enhances folding of N-glycosylated proteins required for cancer cell migration, invasion, and metastasis.